2015
DOI: 10.1091/mbc.e15-03-0165
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Scc2 cohesin deposition complex subunit regulates chromosome condensation through cohesin integrity

Abstract: Cohesin deposition requires the Scc2/Scc4 complex. Scc2 is phosphorylated, and mutations that mimic constitutive phosphorylation lead to inviability and chromosome condensation defects, likely due to reduced Mcd1 levels resulting from compromised cohesin integrity. Thus phosphoregulation of Scc2 has important consequences for chromosome integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…We identified 15 phosphorylation sites in NIPBL/Scc2 required for the association of another SMC complex, cohesin, with chromosomes. It has been reported that the Scc2 phosphorylation state regulates chromosome condensation through cohesin integrity . Therefore, there is a high possibility that the identified phosphorylation sites in NIPBL/Scc2 are involved in the control of mitotic chromosome structure, similarly to those in condensin, TopoIIα, and Kif4.…”
Section: Resultsmentioning
confidence: 99%
“…We identified 15 phosphorylation sites in NIPBL/Scc2 required for the association of another SMC complex, cohesin, with chromosomes. It has been reported that the Scc2 phosphorylation state regulates chromosome condensation through cohesin integrity . Therefore, there is a high possibility that the identified phosphorylation sites in NIPBL/Scc2 are involved in the control of mitotic chromosome structure, similarly to those in condensin, TopoIIα, and Kif4.…”
Section: Resultsmentioning
confidence: 99%
“…Wildtype cells shifted to an elevated temperature during mitosis exhibit rDNA hypercondensation (Shen and Skibbens, 2017a; Matos-Perdomo and Machín, 2018a), but the structural basis for this dramatic change in chromatin structure remains unknown. Cohesins play a critical role in chromosome condensation, including across the rDNA locus, such that mutation in either cohesin subunits (Mcd1/Scc1, Pds5 or Scc3) or regulators (Eco1 or Scc2) all result in severe rDNA condensation defects (Guacci et al, 1997; D’Ambrosio et al, 2008; Tong and Skibbens, 2015; Skibbens et al, 1999; Hartman et al, 2000; Woodman et al, 2015; Orgil et al, 2015). These observations formally suggest that de novo cohesin deposition during mitosis may play a critical role in hyperthermic-induced rDNA hypercondensation, in contrast to the decondensation of rDNA into ‘puffs’ that occurs upon either cohesin inactivation or dissociation (Guacci et al, 1997; Ciosk et al, 2000; Shen and Skibbens, 2017a).…”
Section: Resultsmentioning
confidence: 99%
“…Wild-type cells shifted to an elevated temperature during mitosis exhibit rDNA hypercondensation (Shen and Skibbens 2017a; Matos-Perdomo and Machín 2018a), but the structural basis for this dramatic change in chromatin structure remains unknown. Cohesins play a critical role in chromosome condensation, including across the rDNA locus, such that mutation in genes that encode either cohesin subunits (Mcd1/Scc1, Pds5, or Scc3) or regulators (Eco1 or Scc2) all result in severe rDNA condensation defects (Guacci et al 1997;Skibbens et al 1999;Hartman et al 2000;D'Ambrosio et al 2008;Guacci and Koshland 2012;Orgil et al 2015;Tong and Skibbens 2015;Woodman et al 2015). These observations formally suggest that de novo cohesin deposition during mitosis may play a critical role in hyperthermic-induced rDNA hypercondensation, in contrast to the decondensation of rDNA into "puffs" that occurs upon either cohesin inactivation or dissociation (Guacci et al 1997;Ciosk et al 2000;Shen and Skibbens 2017a).…”
Section: Hyperthermic-induced Rdna Hypercondensation Occurs In the Abmentioning
confidence: 99%